Manufacturing export and ICT infrastructure in West Africa: Investigating the roles of economic and political institutions - Ibukun Beecroft; Evans Osabuohien; Uchenna Rapuluchukwu Efobi; Isaiah Oluranti Olurinola; Romanus A. Osabohien (African Governance and Development Institute (AGDI), 2019)
Investment in ICT infrastructure development is crucial to international trade through its provision of reliable interconnectedness via communication. This can be augmented via institutional intervention, which addresses opportunistic or rent-seeking behaviours of ICT infrastructure providers and reduces operational costs, among others. However, ICT infrastructural provision in West Africa remains low, necessitating the current drive by the regional economic community (ECOWAS) to make some advancement in this regard for enhanced trade outcomes of members. With the aim of unbundling institutional framework in the infrastructure-export nexus, this study empirically examines the relationship between manufacturing export and ICT infrastructure and articulates how economic and political institutions influence such interaction. Focusing on 14 West African countries, the study uses the Systems Generalised Method of Moments (SGMM) technique to address possible issues of endogeneity and reverse causality. The results reveal that in the face of improved economic and political institutions, particularly those related to enforcement of contracts, the influence of ICT infrastructure in strengthening the exporting capacity from the manufacturing sector is greater. In addition, some measures of economic and political institutions matter more than others. The study recommends that ECOWAS countries promote better institutional quality, particularly in terms of transparency, accountability, corruption control, regulatory quality and the rule of law.
Keywords: F14; O14; O17; O43; P45; 330; Dynamic panel data; Infrastructural provision; Infrastructural development; Institutional framework; Institutional quality; Manufacturing export; Manufacturing value added